Analisis Faktor Yang Mempengaruhi Remaja Putri Melakukan Pemeriksaan Payudara Sendiri (Sadari) Di Sma Negeri 25 Kabupaten Tangerang - Damyati, Siti Anggi; Anggraini, Nofa (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
This term is commonly used to refer to the action of self-examination of the breasts by women to detect changes or lumps. Breast self-awareness is a form of early detection for breast cancer that can be independently performed by women. Understanding the factors influencing adolescent girls in performing Breast Self-Examination (BSE) in State Senior High School 25, Tangerang Regency, is the focus of this research. The research design employed is an analytical correlation method with a cross-sectional design. Analytical correlation studies are techniques used to analyze the relationship between independent and dependent variables. The research findings related to the Factors Influencing Adolescent Girls to Perform Breast Self-Examination (BSE) in State Senior High School 25, Tangerang Regency, indicate a significant influence. The P-Value for knowledge level is 0.037 < 0.05, for family support is 0.005 < 0.05, and for Healthcare Provider Support is 0.014 < 0.05, all contributing to the behavior of Breast Self-Examination (BSE) in State Senior High School 25, Tangerang Regency